A Novel and Practical Synthesis of Tryptanthrin - He, Yong; Chen, Shiyun; Gao, Yonghao; Gui, Shuangying; Feng, Yisi (Synthesis, 2022)
Tryptanthrin was synthesized through a two-step reaction of oxidation and condensation in a one-pot method, with isatin and sodium hypochlorite as starting materials. The influence of sodium hypochlorite, acetonitrile dosage, oxidation reaction temperature, and reaction time on the yield of the target product during the reaction was investigated. The following optimal reaction conditions were obtained: the ratio of n (isatin) to n (sodium hypochlorite) was 2:1, and the reaction time was 6–8 hours at room temperature. The structure of tryptanthrin was confirmed by matching the IR, NMR, and mass data with the literature report. The study shows that the chemical reaction route designed in this report is short, with high yield and purity of the target product. Its low production cost and simple operation method are expected to be applicable to industrial production.
Keywords: isatin; sodium hypochlorite; Baeyer–Villiger oxidation rearrangement; tryptanthrin